2010
DOI: 10.1002/adfm.200901764
|View full text |Cite
|
Sign up to set email alerts
|

White Electroluminescence by Supramolecular Control of Energy Transfer in Blends of Organic‐Soluble Encapsulated Polyfluorenes

Abstract: Here, it is demonstrated that energy transfer in a blend of semiconducting polymers can be strongly reduced by non‐covalent encapsulation of one constituent, ensured by threading of the conjugated strands into functionalized cyclodextrins. Such macrocycles control the minimum intermolecular distance of chromophores with similar alignment, at the nanoscale, and therefore the relevant energy transfer rates, thus enabling fabrication of white‐light‐emitting diodes (CIE coordinates: x = 0.282, y = 0.336). In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
49
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 47 publications
3
49
0
Order By: Relevance
“…We note that the HATNA* emission in the blend is characterized by a much stronger 0-0 transition (PL 0-0 / PL 0-1 % 1.06) than in the pure HATNA* thin film, consistently with the expected suppression of aggregation as a result of embedding HATNA* in TFB. 36,37 Emission from TFB is nearly completely suppressed, as expected, as a result of efficient energy transfer from TFB to HATNA* (note that although HATNA*'s absorption spectrum is not very strong at low energies, this does extend so as to provide a significant overlap with emission from TFB, see Fig. 1(c)).…”
mentioning
confidence: 70%
“…We note that the HATNA* emission in the blend is characterized by a much stronger 0-0 transition (PL 0-0 / PL 0-1 % 1.06) than in the pure HATNA* thin film, consistently with the expected suppression of aggregation as a result of embedding HATNA* in TFB. 36,37 Emission from TFB is nearly completely suppressed, as expected, as a result of efficient energy transfer from TFB to HATNA* (note that although HATNA*'s absorption spectrum is not very strong at low energies, this does extend so as to provide a significant overlap with emission from TFB, see Fig. 1(c)).…”
mentioning
confidence: 70%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Among these scaffolds, DNA-cationic surfactant complexes have emerged as intriguing candidates for optoelectronic applications in recent years because of their unique material properties, including solubility in organic solvents and the ability to form thermally stable, transparent films. 1,2 FRET based fluorescence colour tuning, with fluorophores incorporated into various scaffolds including polymers, biomolecules, micelles, supramolecular assemblies and nanoparticles, is a widely investigated approach for white light generation.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that organic-solvent-soluble, conjugated rotaxanes can be blended with other non-rotaxinated semiconductors to fabricate whiteemitting LEDs. [ 15 ] Intriguingly, suppressed exciton dissociation and polaron formation in rotaxanes can be synergistically exploited with suppression of energy transfer to yield ultrabroadband all-plastic optical amplifi ers by exploitation of the spectrally distinct gain bands of the individual polymers. [ 16 ] More generally, rotaxanes provide unique model systems for the investigation of intermolecular interactions in macromolecular materials.…”
mentioning
confidence: 99%